Recent experimental results on level densities for compound reaction calculations - Schiller A.; Massey T.; Brune C.R.; Grimes S.M.; Voinov A.V. (EPJ Web of Conferences, 2012)
Proton evaporation spectra from 6,7Li induced reactions on 54,56,58Fe nuclei have been measured and analyzed with Hauser-Feshbach compound reaction calculations with a Gilbert and Cameron input level density model. Level densities of residual 59-64Ni nuclei have been extracted from proton spectra. Both level density and level density parameter a have been compared against the respective values obtained from neutron resonance spacing data. The discrepancy has been found in systematics behavior of level densities against the mass number of Ni isotopes.